Pulmonary fibrosis secondary to COVID-19: a narrative review. (3rd June 2021) - Tanni, Suzana Erico; Fabro, Alexandre Todorovic; de Albuquerque, André; Ferreira, Eloara Vieira Machado; Verrastro, Carlos Gustavo Yuji; Sawamura, Márcio Valente Yamada; Ribeiro, Sergio Marrone; Baldi, Bruno Guedes
ABSTRACT: Introduction: Coronavirus disease 2019 (COVID-19) is still increasing worldwide, and as a result, the number of patients with pulmonary fibrosis secondary to COVID-19 will expand over time. Risk factors, histopathological characterization, pathophysiology, prevalence, and management of post-COVID-19 pulmonary fibrosis are poorly understood, and few studies have addressed these issues.Areas covered: This article reviews the current evidence regarding post-COVID-19 pulmonary fibrosis, with an emphasis on the potential risk factors, histopathology, pathophysiology, functional and tomographic features, and potential therapeutic modalities. A search on the issue was performed in the MEDLINE, Embase, and SciELO databases and the Cochrane library between 1 December 2019, and 25 January 2021. Studies were reviewed and relevant topics were incorporated into this narrative review. Expert opinion: Pulmonary sequelae may occur secondary to COVID-19, which needs to be included as a potential etiology in the current differential diagnosis of pulmonary fibrosis. Therefore, serial clinical, tomographic, and functional screening for pulmonary fibrosis is recommended after COVID-19, mainly in patients with pulmonary involvement in the acute phase of the disease. Further studies are necessary to determine the risk factors, markers, pathophysiology, and appropriate management of post-COVID-19 pulmonary fibrosis.